2005
DOI: 10.1360/062004-37
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Eethylene influences flower opening of cut roses (Rosa hybrida) by regulating the genes encoding ethylene biosynthesis enzymes

Abstract: The purpose of this paper is to investigate the differential responses of flower opening to ethylene in two cut rose cultivars, 'Samantha', whose opening process is promoted, and 'Kardinal', whose opening process is inhibited by ethylene. Ethylene production and 1-aminocyclopropane-1-carboxylate (ACC) synthase and oxidase activities were determined first. After ethylene treatment, ethylene production, ACC synthase (ACS) and ACC oxidase (ACO) activities in petals increased and peaked at the earlier stage (stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 22 publications
1
70
0
Order By: Relevance
“…The opening process of cut rose flowers can be divided into six stages (Ma et al, 2005). The expression patterns of RhPR10.1 in all the floral organs, including sepal, stamen, pistil, petal, and receptacle, showed similar trends, with transcript levels increasing progressively from the partially opened flower bud (stage 1) to the onset of petal wilting (stage 6; Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The opening process of cut rose flowers can be divided into six stages (Ma et al, 2005). The expression patterns of RhPR10.1 in all the floral organs, including sepal, stamen, pistil, petal, and receptacle, showed similar trends, with transcript levels increasing progressively from the partially opened flower bud (stage 1) to the onset of petal wilting (stage 6; Fig.…”
Section: Resultsmentioning
confidence: 84%
“…It is well known that ethylene promotes rose flower senescence (Ma et al, 2005), while CTKs delay the process (Mayak and Halevy, 1970;Lukaszewska et al, 1994). Here, we report that an ethyleneinduced rose PR-10 family gene, RhPR10.1, inhibits Figure 1.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Flower-opening stages were defined as described by Ma et al (2005). The flowers were delivered to the laboratory within 1 h of harvest.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Henskens et al (1994) has suggested that the gene might encode a non-functional enzyme; however, the positive correlation between CARAS1 abundance and stylar ethylene production during aging is indicative of the fact that CARAS1 does encode a functional enzyme (Have and woltering, 1997). Ma et al (2005) while studying the differential induction features of three ACS genes in roses found that Rh-ACS2 is strongly induced by senescence. The tissue specificity of Rh-ACS2 has been found to be quickly induced by ethylene in gynoecia (Xue et al 2008).…”
Section: Genes Involved In Ethylene Synthesis (Acc Synthase and Acc Omentioning
confidence: 99%